Surgical Safety Checklist Completeness and Risk Factors for Surgical Site Infection in Panyabungan Regional Hospital - Rizki Fauzan Ghali Nasution; Donal Nababan; Frida Lina Tarigan; Kesaktian Manurung; Janno Sinaga (Jurnal Ners, 2026)
ABSTRACT Surgical site infection (SSI) is a major postoperative complication that increases morbidity, mortality, and healthcare burden. The implementation of the Surgical safety Checklist (SSC) is considered a key preventive strategy, yet its effectiveness remains debated. This study aimed to analyze the association between SSC completeness and SSI, as well as other clinical factors, among surgical patients at RSUD Panyabungan. A cross-sectional design was applied with total sampling of 873 surgical patients from January to April 2025. Data were obtained from medical records and analyzed using multivariate logistic regression. The incidence of SSI was 5.6%. Compliance with SSC was relatively high: Sign In 79.4%, Time Out 80.6%, and Sign Out 80.3%. Bivariate analysis revealed that incomplete SSC in all phases was significantly associated with increased SSI risk (crude OR 6–19; p<0.001). Additional factors such as ≥2 comorbidities (OR 7.02; p<0.001), and emergency surgery (OR 2.99; p=0.006) were also associated with SSI. In the final logistic regression model, independent predictors of SSI were: complete Sign In as a strong protective factor (AOR=0.057; 95% CI: 0.027–0.120; p<0.001), ≥1 comorbidity (AOR=3.075; 95% CI: 1.803–5.246; p<0.001), and emergency surgery compared to elective procedures (AOR=4.274; 95% CI: 1.612–11.335; p=0.003). This study highlights the strong association between Sign In completeness and lower SSI risk, and emphasizes the need for optimizing perioperative management among patients with comorbidities and those undergoing emergency surgery. Keywords: Surgical safety checklist; Surgical site infection; compliance; comorbidity; emergency surgery;